Comparison of the effects of endurance and endurance‑strength training programmes on the level of endothelial dysfunction in women with abdominal obesity: study protocol for a randomised controlled trial: A study protocol of the ENDOFIT study (Journal of Medical Science, 2019)
The primary objective of the study is to compare the effect of endurance and endurance‑strength training on endothelial function in women with abdominal obesity. The secondary objectives include the assessment of the effect of both types of training on anthropometric, densitometric and biochemical parameters. In total, at least 100 women will be recruited for the study. The study population will be randomly divided into two groups according to the type of training: endurance and endurance‑strength training. During the 3-month of intervention, both groups will be performed three times a week training of an equal exercise volume and duration of 60 minutes. Before and after the intervention selected anthropometric and densitometric parameters will be measured and body composition will be analysed. In addition, biochemical parameters related to glucose and insulin homeostasis, lipid metabolism, antioxidant status, oxidative stress, inflammatory markers and endothelial function will be assessed.